KONSELING TRAUMATIK DALAM PENDIDIKAN ISLAM - Hanton (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2019)
Humans as living things that live in this world are never separated from problems and severe events that sometimes can not afford to face them. Events experienced by these individuals can cause excessive fear and can be called a life of trauma called trauma. Trauma is an abnormal mental state or behavior as a result of mental stress or physical injury. Trauma experienced by individuals must be addressed immediately so as not to cause a bigger problem later, a counselor is very instrumental in providing services to individuals who experience trauma which is also called traumatic counseling.